Early Effects of Home Health Value-Based Purchasing on Quality Star Ratings. (December 2021) - Teshale, Salom M.; Schwartz, Margot L.; Thomas, Kali S.; Mroz, Tracy M.
The Home Health Value-Based Purchasing Model (HHVBP) is a new Medicare model wherein home health agencies compete to achieve higher reimbursements by demonstrating improved value according to clinical and patient experience-related quality measures. Many measures used in HHVBP overlap with measures used in quality star ratings for home health agencies. Thus, improvements in quality measures used in HHVBP may also be reflected in changes in star ratings. However, it is unclear whether agencies competing in HHVBP improve their Centers for Medicare & Medicaid Services star ratings compared with those not competing. Using publicly available data from Centers for Medicare & Medicaid Services, we evaluated the effect of HHVBP on quality of patient care and patient experience composite star ratings over a 2-year period using a difference-in-differences analysis. We found evidence for a small, statistically significant increase in quality of patient care star ratings for agencies participating in HHVBP, and no effect on patient experience ratings.